The effect of self-assessment systems, tax knowledge, and tax sanctions on the culture of taxpayer compliance of personal persons - Yana Hendayana; Radhi Abdul Halim Rachmat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine the effect of the self-assessment system, knowledge of taxation, and tax sanctions on individual taxpayer compliance at the Pratama Bandung Cibeunying Tax Service Office. The research population is an individual taxpayer domiciled in the city of Bandung with a sample of 96. The research method involved distributing questionnaires and analytical techniques using multiple linear regression analysis assisted by the SPSS application program. The results show that partially self-assessment systems and tax knowledge have a positive effect on individual taxpayer compliance, while tax sanctions have no effect on individual taxpayer compliance, but simultaneously self-assessment systems, tax knowledge, and tax sanctions have a relatively small effect. That is equal to 11.3% of individual taxpayer compliance, while 88.7% is influenced by other variables not examined.